Validation of a specific phobia questionnaire by University students in Malaysia - NKA, Ismail; AH, Azil; N, Ahmad; S, Sharip (Pusat Perubatan Universiti Kebangsaan Malaysia, 2023)
Specific phobia is a subcategory of anxiety disorders that remains poor understanding due to inadequate screening tools. This study aimed to develop and validate a new Specific Phobia Questionnaire (SPQ). This SPQ was developed based on literature reviews and inputs from related experts for content validity. The SPQ questionnaire consisted of 14 items and after content validity and face validity testing procedure, 12 items were chosen for the final questionnaire. The questionnaire was then distributed via Google form to university students in Klang Valley. A total of 267 students participated in this study with 70.8% were female with mean age of 23.28 (Standard deviation of 4.98) years. Validity analysis using exploratory factor analysis from the final study indicated that the Kaiser-Meyer- Olkin value was 0.77 and extracted three domains; animals, blood injection injury and situational-environment. Reliability analysis showed that Cronbach’s α values were 0.84, 0.86, 0.78 and 0.72 for the total items, animal, blood injection injury and situational-environment domains, respectively. The newly developed SPQ showed good reliability and validity for evaluating specific phobia.